Quantitative volumetric Raman imaging of three dimensional cell cultures - Charalambos Kallepitis (Nature Portfolio, 2017)
Advances in chemical imaging capability can add to our understanding of complex cellular systems. Here the authors develop a framework for label-free quantitative volumetric Raman spectroscopic imaging and use it to visualize and quantify biomolecules in various 3D cellular systems.